Change of earth environment due to the decreasing geomagnetic field -The necessity of observation in Brazilian geomagnetic anomaly region- - Kazuo Makita (Antarctic Record, 1996)
According to recent research on rock magnetism, the geomagnetic field intensity of our planet has been monotonically decreasing for one thousand years and it will disappear after another 1000years if the present decreasing rate continues. It should be noted that the decreasing rate of the geomagnetic field near South America has been remarkably large. Since the total intensity of the geomagnetic field in this region is already very weak, the geomagnetic field near South America will disappear within 400years. It is well known that earth magnetic poles have been frequently reversed during the long earth history. When the earth magnetic poles reverse, the intensity of the geomagnetic field becomes very weak. Therefore, it is considered that human beings will have to live under an extremely weak geomagnetic field in the future. From particle observations by satellite, a large quantity of radiation belt particles (>MeV) are precipitating into Brazilian area on account of the very weak geomagnetic field. These high energy particles, precipitating to a few tens of kilometers altitude, are radiating X-rays. If the decrease of the geomagnetic field continues, these particle precipitations will increase and the area of such phenomena will expand near the future. Fortunately, these particles and X-rays do not reach the ground because they are absorbed by the atmosphere. However, there may be a possibility that several electro-magnetic waves occurring in the upper atmosphere reach the ground. Furthermore, it is reported that high energetic solar protons induce the destruction of the ozone layer in the polar cap. So these precipitating particles may also influence the depletion of ozone in the Brazilian anomaly region. The objective of our study is to examine the future earth's environment when the geomagnetic field becomes very weak. We can predict the future earth environment by investigating the upper atmosphere phenomena in the Brazilian region because the geomagnetic field intensity in Brazil is already extremely weak.